2013
DOI: 10.1002/jmv.23779
|View full text |Cite
|
Sign up to set email alerts
|

Coexistence of hepatitis B surface antigen and antibody to hepatitis B surface may increase the risk of hepatocellular carcinoma in chronic hepatitis B virus infection: A retrospective cohort study

Abstract: The simultaneous detection of hepatitis B surface antigen (HBsAg) and antibody to hepatitis B surface (anti-HBs) is unusual in chronic hepatitis B virus (HBV) infection, but may be related with more advanced liver diseases. This retrospective long-term cohort study was aimed to investigate whether coexistence of HBsAg and anti-HBs may increase the risk of hepatocellular carcinoma (HCC) in chronic HBV infection. A total of 1,042 non-HCC patients were recruited and followed up for a median 4.3 years (range 1.0-2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
49
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(56 citation statements)
references
References 30 publications
6
49
0
1
Order By: Relevance
“…A retrospective cohort study has shown that HBeAg and HBV DNA persist for several decades in most carriers, and their risk of hepatocellular carcinoma (HCC) is increased. 20 Fortunately, the HBsAg disappeared and HBeAg seroconversion was achieved in this patient, who eventually cleared the HBV and recovered.…”
Section: Discussionmentioning
confidence: 67%
“…A retrospective cohort study has shown that HBeAg and HBV DNA persist for several decades in most carriers, and their risk of hepatocellular carcinoma (HCC) is increased. 20 Fortunately, the HBsAg disappeared and HBeAg seroconversion was achieved in this patient, who eventually cleared the HBV and recovered.…”
Section: Discussionmentioning
confidence: 67%
“…No NA resistance-related primary mutations were found, which is in accordance with the treatment-naive HBV-infected samples. The pathogenesis of coexisting HBsAg and anti-HBs antibodies remains unclear; however increasing evidence suggests that the coexistence of HBsAg and anti-HBs antibodies is associated with the severity of liver disease and the active replication/reactivation of virus 6, 8, 39 . Mutations of the core promoter (CP) and precore are prevalent in HBV chronic infection 40 and the severity of liver disease associated with core promoter (T1753C, A1762T, G1764A, T1768A and A1846T/C) and precore (G1896A and G1899A) mutations has been widely discussed 4144 .…”
Section: Discussionmentioning
confidence: 99%
“…Hence it is a conundrum when both HBsAg and anti-HBs are present in same serological profile 5 . However, incidences of coexisting of HBsAg and anti-HBs among HBsAg positive patients has been increasingly reported, which is nearly 5% in China 5 , 21% in Japan 6 , 36% in Netherlands 7 , 2.8% in France 8 , 2.9% in South Korea 9 , varies from 2.8% to 36% 510 and progressively increases with patient age from 40 to 70 years old 11 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Coexistence of HBsAg and anti‐HBs is uncommon, but has been described during resolution of acute HBV infection, in HBV carriers exposed to heterologous subtypes of HBsAg, and in patients with chronic HBV infection and serious liver disease . Its prevalence ranges in different populations from 2% to 7% of HBsAg positive (HBsAg[+]) patients . The variability of HBV strains in cases of HBsAg and anti‐HBs coexistence has been linked to higher variability of the N‐terminal region, the major hydrophilic region (MHR) of the small hepatitis B surface antigen (SHB), the preS region, and the reverse transcriptase region (RT) .…”
Section: Introductionmentioning
confidence: 99%